2011
DOI: 10.1016/j.exger.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of a common LAMA5 variant with anthropometric and metabolic traits in an Italian cohort of healthy elderly subjects

Abstract: Laminins are large heterotrimeric glycoproteins found in basement membranes where they play an essential role in cell-matrix adhesion, migration, growth, and differentiation of various cell types. Previous work reported that a genetic variant located within the intron 1 of LAMA5 (rs659822) was associated with anthropometric traits and HDL-cholesterol levels in a cohort of premenopausal women. The present study aimed to investigate the effect of LAMA5 rs659822 on anthropometric traits, lipid profile, and fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
2
4
1
Order By: Relevance
“…interactions and matrix-mediated cellular signaling cascades impacts the decline of age-dependent physiological performance and thereby life span (Goddeeris et al, 2003;Hansen et al, 2005;Wolfson et al, 2009;De Luca et al, 2010;De Luca et al, 2011;Wilson et al, 2013;Nishimura et al, 2014). Consistently, here we report that common genetic variants in the SDC4 gene affect human longevity.…”
Section: Growing Evidence From Model Systems and Humans Suggest That supporting
confidence: 87%
“…interactions and matrix-mediated cellular signaling cascades impacts the decline of age-dependent physiological performance and thereby life span (Goddeeris et al, 2003;Hansen et al, 2005;Wolfson et al, 2009;De Luca et al, 2010;De Luca et al, 2011;Wilson et al, 2013;Nishimura et al, 2014). Consistently, here we report that common genetic variants in the SDC4 gene affect human longevity.…”
Section: Growing Evidence From Model Systems and Humans Suggest That supporting
confidence: 87%
“…Here, we report an association of LAMA5 rs659822 with inter-individual variability in fasting plasma glucose levels among pre-and early pubertal children. The effect of rs659822 on fasting glucose levels was previously seen in a Caucasian cohort of elderly subjects [8]. Additionally, in line with our previous findings in pre-menopausal women [7], the present study provides evidence of an association between LAMA5 rs944895 and fasting serum TG in children.…”
Section: Discussionsupporting
confidence: 92%
“…But considering that only two common polymorphisms were investigated in this study, we cannot exclude the possibility that other variants in LAMA5 could contribute to variation in this trait. Also, in our cohort of children we did not observe the previously reported associations between rs659822 and variation in anthropometric or body composition phenotypes [7,8]. This could be explained by a lack of power in our study as suggested by the marginal association (P < 0.071) observed between rs659822 and body weight ( Table 2).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations